Kuliah Kerja Nyata (KKN) during the Covid-19 Pandemic as a Form of Community Service - M. Ilham Lutfi (Pena Cendekia Insani, 2020)
The pandemic not only presents anxiety about health threats, but alsothe welfare of many employees due to layoffs. Some of small, mediumand even large scale businesses were forced to go out of business.State Islamic University of North Sumatra immediately respondedpositively to the impact that emerged in the community due to theCovid-19 pandemic by holding Community DevelopmentParticipation to online with 4 theme